Factors associated with maternal postpartum fatigue: an observational study - Henderson, J; Alderdice, F; Redshaw, M (BMJ Publishing Group, 2019)
OBJECTIVES:To assess the prevalence of postpartum fatigue at 10 days, 1 month and 3 months, and to describe the sociodemographic and clinical characteristics of women with fatigue and the associations with infant characteristics, maternal-infant attachment, and partner and midwifery support. SETTING:Maternity care in England. Secondary analysis of 2014 National Maternity Survey. PARTICIPANTS:Participants were a random sample of 10 000 women selected by the Office for National Statistics using birth registration records. Women aged less than 16 years or if their baby had died were excluded. Questionnaires were sent to women at 3 months post partum and asked about well-being and care during pregnancy, labour, birth and post partum. Specifically, women were asked whether they experienced fatigue/severe tiredness at 10 days, 1 month or 3 months post partum. Responses were received from 4578 women (47% response rate). RESULTS:Decreasing but substantial proportions of women, 38.8%, 27.1% and 11.4%, experienced fatigue/severe tiredness at 10 days, 1 month and 3 months, respectively. These figures varied significantly by maternal age, level of deprivation, education and parity. Women reporting depression, anxiety, sleep problems and those breast feeding were at significantly increased risk (eg, OR for depression in women with fatigue at 3 months: 2.99 (95% CI 2.13 to 4.21)). Significantly more negative language was used by these women to describe their babies, and they perceived their baby as more difficult than average (eg, two or more negative adjectives used by women with fatigue at 3 months: OR 1.86 (95% CI 1.36 to 2.54)). Women with postpartum fatigue had greater partner support but were significantly less likely to report seeing the midwife as much as they wanted. CONCLUSIONS:Postpartum fatigue is not inevitable or universal, although early in the postnatal period it affects a substantial proportion of women. Predictors include age and parity, but practical help and support from partners and midwives may be protective factors.